Changes in mountainous runoff in three inland river basins in the arid Hexi Corridor, China, and its influencing factors. (October 2019) - He, Yi; Jiang, Xiaohui; Wang, Ninglian; Zhang, Shiqiang; Ning, Tingting; Zhao, Yan; Hu, Yiyi
Highlights: The contribution of precipitation and the underlying surface changes to runoff were equal in the upper reaches of the Shule River. The underlying surface changes are the main reason for runoff variation at the headwater region of the Shiyang River. Precipitation are the major contributor to the runoff increase in the upper reaches of the Hei River. Abstract: Quantitatively distinguishing control factors to runoff change is important for water resource management. The Mann-Kendall trend test, Pettitt test and Budyko framework were used to identify the impacts of climate and the underlying surface changes on runoff in the upper reaches of three inland river basins in Northwest China from 1960 to 2012.The results show that the annual runoff in three inland river basins increased, but only the Shule River and Hei River reached significant levels. The abrupt changes in the annual runoff in the upper reaches of the Shule River, Hei River and Shiyang River occurred in 1997 ( p <0.05), 1979 ( p <0.05) and 2002 ( p >0.05) respectively. In the upper reaches of the Shule River basin, the contributions of precipitation and of the underlying surface changes to runoff were equal, accounting for approximately 50% of the total. The contribution of precipitation to runoff change in the upper reaches of the Hei River basin is 58% and that of the underlying surface is approximately 42%. In the upper reaches of the Shiyang River, the contributions of the underlying surface and of precipitation to runoff were 64% and 37%, respectively. This study can provide a scientific basis for formulating climate change coping strategies.